Comparative study of sustained-release lipid microparticles and solid dispersions containing ibuprofen - Hugo Almeida; Maria Helena Amaral; Paulo Lobão (Universidade de São Paulo, 2012)
Ibuprofen is one of the most important non-steroidal anti-inflammatory drugs used in the treatment of inflammatory diseases. In its pure state, ibuprofen presents poor physical and mechanical characteristics and its use in solid dosage forms needs the addition of excipients that improve these properties. The selection of the best excipients and the most suitable pharmaceutical dosage form to carry ibuprofen is very important for the industrial success of this drug. Given these factors, lipid microparticles and solid dispersions of ibuprofen with cetyl alcohol, stearic acid, and hydrogenated castor oil were prepared. These formulations were intended to improve the physical and mechanical characteristics and to sustain the release of this drug. Physical mixtures were also prepared with the same ingredients in similar proportions. The solid dispersions of ibuprofen/stearic acid and ibuprofen/hydrogenated castor oil showed the best flow characteristics compared with pure ibuprofen. Further, gelatin capsules filled with lipid microparticles and solid dispersions were submitted to dissolution tests in order to study the influence of the prepared systems in the release profiles of ibuprofen. Prolonged release of ibuprofen was achieved with the lipid microparticles and solid dispersions prepared with the different types of excipients. O ibuprofeno é um dos antiinflamatórios não esteróides mais utilizados no tratamento de patologias associadas a processos inflamatórios. Este fármaco, quando no seu estado puro, apresenta características físicas e mecânicas pouco satisfatórias e a sua utilização em formas sólidas só é possível se forem adicionados excipientes que permitam melhorar estas propriedades. A seleção dos excipientes ideais e da forma farmacêutica mais adequada para veicular o ibuprofeno é fundamental para o sucesso industrial deste fármaco. Tendo em conta estes fatores, prepararam-se micropartículas lipídicas e dispersões sólidas de ibuprofeno com cada um dos seguintes excipientes: álcool cetílico, ácido esteárico e óleo de rícino hidrogenado. Estas formulações tinham por finalidade melhorar as características físicas e mecânicas e prolongar a liberação deste fármaco. Foram, também, preparadas misturas físicas do ibuprofeno com os mesmos excipientes e nas mesmas proporções. As dispersões sólidas de ibuprofeno/ácido esteárico e as dispersões sólidas de ibuprofeno/óleo de rícino hidrogenado foram aquelas que apresentaram melhores características de escoamento comparativamente com o ibuprofeno puro. Por outro lado, foram preparadas cápsulas de gelatina com as diferentes micropartículas lipídicas e dispersões sólidas e submetidas a ensaios de dissolução com o objetivo de estudar a influência dos sistemas preparados nos perfis de liberação do ibuprofeno. A liberação prolongada do ibuprofeno foi conseguida nas diferentes micropartículas lipídicas e dispersões sólidas preparadas com os diferentes excipientes.